Design and Implementation of Solder Paste Dispenser Based on Linear Drive System - Riky Tri Yunardi; Moh. Zakky Zulfiar; Rr. Wanda Auruma Putri; Deny Arifianto (Muhammadiyah University, Sidoarjo, 2019)
In the technology to create prototypes for electronic hardware is usually constructed using surface mount device printed circuit board (SMD PCB). In this paper introduces the design and implementation of low-cost electrical solder paste dispenser that supports the PCB solder process. The design consists of a nozzle and linear drive systems based on stepper motors operating with electric power to push the plunger down to drop the solder paste on the board. To test the performance of solder paste that has been designed verified by experiment. Solder paste dispenser design was tested using SMD resistor with the solder pads of different sizes for R0603, R0805, and R1206 on PCB. The results showed that the design of the prototype was able to put the pasta in various field pads between 0.54 mm2, 0.91 mm2 and 1.44 mm2 for standard solder pads with an error in the 2% - 5%. Based on the results, the device has been shown to potentially be used to attach electronic components to printed circuit boards.